A compact antenna with frequency and pattern reconfigurable characteristics. Issue 11 (November 2015) - Pan, Yong; Ma, Yongta; Xiong, Jiang; Hou, Ziye; Zeng, Yue
ABSTRACT This article proposes a compact printed frequency and pattern reconfigurable antenna. The antenna has a low profile, low cost, and small size of 58.0 × 40.0 × 1.2 mm3, and mainly consists of dual symmetrical radiators, two rectangle parasitic elements and one inverted T‐shape ground plane which may acts as a reflector. By loading the parasitic elements and selecting different radiators to connect to the feed, the proposed antenna can switch among three operating frequencies (2.01–2.26 GHz, 2.28–2.52 GHz, and 3.73–4.02 GHz) and select patterns between two kinds of radiating patterns with main lobe directions of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2gd6g4ss" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />φ=90°</alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2gd6g5q6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />φ=270°</alternatives> in the xoy plane. Comparing the expected results with measured results, a good agreement is obtained. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2467–2471, 2015